Кількісна оцінка каталазної активності вуглецевих сорбентів медичного призначення - Глевацька, К.В.; Бакалінська, О.М.; Картель, М.Т. (Видавничий дім "Академперіодика" НАН України, 2008)
The kinetics of catalytic reactions of hydrogen peroxide decomposition in water solutions by carbon adsorbents of the SCN and KAU type which are used as hemo- and enterosorbents and their modified forms (oxidized in H- and Fe(III)-form) at different values of pH in comparison with the activity of catalase is investigated. The enzyme kinetics laws are applied to the description of hydrogen peroxide decomposition processes. The dependence of the Michaelis–Menten constant on pH for the reactions which are accelerated by the investigated materials and catalase is determined. It is shown that sorbents of the SCN and KAU type demonstrate a greater catalytic activity than catalase outside of the enzyme pH optimum value. This fact can be used in efferent medicine and biotechnology.